Reflectance anisotropy spectroscopy of Fe3O4(110): Anisotropic strain - Fleischer, Karsten; Walls, Brian; Shvets, Igor; WALSHE, KILLIAN; Zhussupbekova, K.; Lübben, O/ (My University, 2018)
We present a study of (110)-terminated magnetite using a range of surface-sensitive techniques, the foremost of those being reflectance anisotropy spectroscopy (RAS). The anisotropic optical response of the as-polished and row-reconstructed terminations are investigated. The responses are interpreted to result from termination-induced anisotropic shifts in energy of the bulklike optical transitions. Density functional theory (DFT) calculations demonstrate that the row reconstruction of Fe3O4(110) exhibits anisotropic strain in its terminating layers, and this strain is concluded to be the origin of the RAS response. X-ray photoelectron spectroscopy measurements demonstrate that the row reconstruction is reduced and the stoichiometry in the surface region is relatively easily altered by in situ preparation procedures. This is correlated to altered surface electronic properties identified by scanning tunneling spectroscopy measurements. RAS is sensitive to this change in surface structure, with the magnitude of the RAS response being altered.
PUBLISHED
Keywords: Surface and interfacial phenomena; Surface reconstruction; Spinel; Density functional theory; Reflectivity; Scanning tunneling microscopy